2013
DOI: 10.4161/auto.26505
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a lung defect in autophagy-deficient mouse strains

Abstract: Yeast Atg1 initiates autophagy in response to nutrient limitation. The Ulk gene family encompasses the mammalian orthologs of yeast ATG1. We created mice deficient for both Ulk1 and Ulk2 and found that the mice die within 24 h of birth. When found alive, pups exhibited signs of respiratory distress. Histological sections of lungs of the Ulk1/2 DKO pups showed reduced airspaces with thickened septae. A similar defect was seen in Atg5-deficient pups as both Ulk1/2 DKO and Atg5 KO lungs show numerous glycogen-lad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 44 publications
5
51
0
Order By: Relevance
“…The existence of a negative feedback loop between ULK1/2 and mTOR is further confirmed by the presence of activated mTOR in ULK1/2 double knock-out mice (50). Further, it has been shown that ULK1 and ULK2 inhibit mTORC1 by binding to and phosphorylating the raptor, the regulatory-associated protein of mTOR (51).…”
Section: Discussionmentioning
confidence: 84%
“…The existence of a negative feedback loop between ULK1/2 and mTOR is further confirmed by the presence of activated mTOR in ULK1/2 double knock-out mice (50). Further, it has been shown that ULK1 and ULK2 inhibit mTORC1 by binding to and phosphorylating the raptor, the regulatory-associated protein of mTOR (51).…”
Section: Discussionmentioning
confidence: 84%
“…Although the ULK1/2 complex is required for autophagy induction in response to amino acid deprivation, autophagy is potently induced by glucose deprivation and ammonia, and more mildly with rapamycin treatment in ULK1/2 deficient cells, suggesting that autophagy regulation and mTOR signaling include a ULK independent pathway (21, 23-25). We therefore investigated whether mTORC1 regulation of autophagy by eIF2Ī± phosphorylation was independent of ULK1/2 activity.…”
Section: Resultsmentioning
confidence: 99%
“…S6D in the supplemental material). Second, the phenotype of ULK1/2 DKO mice is milder than that of Atg13 KO and FIP200 KO mice: ULK1/2 DKO mice die after birth (28). These milder effects of deletion of ULK1 and ULK2 may indicate that they are not essential for the function of Atg13 and FIP200 in certain settings.…”
Section: Discussionmentioning
confidence: 98%
“…Although mice lacking either ULK1 or ULK2 are viable, ULK1/2 double-knockout (DKO) mice die during the neonatal period (28). In addition, FIP200 is involved in various signaling pathways, including those of p53, focal adhesion kinase (FAK), Pyk2, tumor necrosis factor alpha (TNF-ā£)-Jun N-terminal protein kinase (JNK), tuberous sclerosis complex (TSC)-mTOR, transforming growth factor beta (TGF-ā¤), and ā¤-catenin (29)(30)(31).…”
mentioning
confidence: 99%